LITHOPROBE: Faults and Fluids - Fyfe, W.; Kerrich, R.; Hicock, S.; Colloza, F. (Geoscience Canada, 1987)
Abstract Data are reported on fluid activity along two major structures covered by LITHOPROBE seismic reflection traverses — Vancouver Island and Kapuskasing. Major faults on Vancouver Island are characterized by sporadic Mn-oxides (s 17 weight percent (wt.%)) orcarbonate-hydrocarbon mineralization. Mn-oxides have infiltrated disturbed glaciogenic sediments (s 30 ka) interpreted as projections of bedrock faults into Quaternary cover. Fault carbonates are characterized by a distinctive trace element composition including enhanced abundances of V (40-146 ppm), Co(11-31 ppm), Ni (32-70 ppm) and Zn (39-86 ppm); and the hydrocarbons possess elevated V (146-603 ppm), Ni (60-210 ppm) and Zn (26-80 , 3Cspans-14 to 0 per mil (%o), implying some reduced Cin the source region. Fault mineralization is interpreted as the product of the distillation of volatiles and solutes off the Juan de Fucaplate during subduction. Such fluid refluxing in continental margin faults may account for some of the disparity in the global budget ofwater calculated to be a net flux of 1.2-11 ÷ 10<4g »yr ' into the mantle. Fluid activity in the Kapuskasing thrust belt is dominated by carbonatization and retrograde hydration reactions in ductile shear zones, pseudotachylite, and granitic melts generated by decompression accompanying uplift.